Palladium(II) complexes of aminothiazole‐based phosphines: Synthesis, structural characterization, density functional theory calculations and catalytic application in heck reaction. (26th April 2017) - Gholivand, Khodayar; Kahnouji, Mohammad; Mark Roe, S.; Gholami, Akram; Fadaei, Farzaneh T.
Abstract : Three Pd(II) complexes of some hemilabile ligands, aminothiazole‐based phosphines, were synthesized to investigate the catalytic activity of them in Heck cross‐coupling reactions. The crystal structures of complexes PdCl2 [(Ph2 P)HN(C3 H2 NS)] (C 1 ) and PdCl2 [(Ph2 P)HN(C7 H4 NS)] (C 3 ) were determined using X‐ray crystallography, which reveals that the ligand coordinates in a chelating mode through P and N (endocyclic) atoms in square planar geometry. Experimental and theoretical studies (atoms in molecules and natural bond orbital analyses) show that the Pd(II) interacts more strongly with the P atom than the N atom in the chelated ligand, N^P. This trait can promote catalytic activity of the complexes in comparison with our previous work in which chelated ligands with two phosphorus atoms, P^P, were used. The influence of non‐covalent intermolecular interactions on the assembly of the solid‐state structures is also discussed in terms of geometrical analysis. The prepared complexes turn out to be useful pre‐catalysts in Heck cross‐coupling reactions owing to the coordinative flexibility of the hemilabile ligands. The protocol affords the corresponding products in greater yield than the same reactions with bis(phosphino)amine Pd(II) complexes, as the catalysts in our previous work. Abstract : Synthesis of three Pd(II) complexes with some aminothiazole‐based phosphines. Molecular structure and crystal packing of the complexes were investigated. They represent high catalytic activity in the Heck coupling reactions owing to the coordinative flexibility of the hemilabile ligand.